DIFFERENCES IN ROUGH MOTORIC DEVELOPMENT, LANGUAGE AND PROSOCIAL BEHAVIOR IN CHILDREN WHO KINDERGARTEN PROGRAM FULL DAY AND REGULAR IN 2019 - Isyos Sari Sembiring (Excellent Midwifery Journal, 2020)
The background of this research is Targeted SDGs of quality education by 2030 ensure that all children have access to quality early development, care, and pre-primary education.The purpose of this study is to find out the differences in Roughmotoric, language and prosocial behavior development in children undergoing kindergarten and regular daytime kindergarten learning.Types and designs in this study use Mixed Methods namely Sequential Explanatory Designs. Population in Quantitative Research children aged 4-6 years who attend learning in kindergarten and regular programs, and qualitative research populations School Leaders, Teachers/Teaching Staff, parents. Quantitative research sample is 34 respondents in Full Day program Kindergarten and 38 people in Regular program and for Qualitative research are School Leaders, Teachers / Teaching Staff, parents, sample technique in Quantitative research is Total Sampling, and for Qualitative research is proportional simple random sampling. Examination using KPSP and prosocial behavior observation sheets in quantitative research, and in qualitative research using interview guides and focus group discussion guides. Data analysis in quantitative research uses Mann Whitney and qualitative research uses data reduction analysis techniques, data display and conclusion drawing / verification.The results of quantitative research on bivariate analysis showed that there were significant differences between children undergoing full-day and regular program kindergarten.  On p-value motor development was 0.008 (p <0.05), language p-value was 0.006 (p <0.05) and prosocial behavior p-value was 0.009 (p <0.05). Qualitative research results are not found any obstacles and efforts have been made to improve the quality of Roughmotoric development, language and prosocial behavior, so that it has benefited and achieved expectations of Roughmotoric development, language and prosocial behavior in children undergoing kindergarten full and regular programs.The conclusion of this study is Roughmotoric, language, and prosocial behavior development. in children who undergo full-day kindergarten program is better than regular program kindergarten.Keywords: Language development, rough motor development, prosocial behavior,kindergarten